Trabalho, aposentadoria e envelhecimento: entre os caminhos da (in)segurança social e das (in)certezas pessoais. Um estudo com docentes da Universidade Federal de Goiás - Cézar, Adriane Geralda Alves do Nascimento (2018)
This thesis aimed to understand the meanings assumed by the continuum of postretirement work, the meanings of retirement and the experience of aging, for a specific category of analysis: the professors of the Federal University of Goias, aged 60 or over, who even as retirees, remain active in the labor market. For this, the work was structured through bibliographical research that focused on themes related to the emergence of salary conditions, social protection, the main transformations suffered by the work, more specifically Fordism to flexible accumulation, the political context of some regimes in Brazil and its importance for the consolidation of labor rights. The reflections followed with discussions also related to the history of social security and retirement. The theoretical articulation was anchored by conducting a qualitative field research, using in-depth interviews, using a semi-structured script, applied to a sample of seventeen interviewees, composed of UFG professors, already retired, in the June and July 2017, were recorded and transcribed and then analyzed. Hermeneutics was adopted in depth as a technique of analysis. The general results showed that for the analyzed category, much more than a financial return, work meant and means source of motivation, achievement, socialization, pleasure, health and life continuum. However, retirement did not bring any significant milestone, for all the interviewees. They just said they had continued to work and did not feel the retirement as a moment of strong transition. Retirement was considered not as the end of a cycle, but as a new cycle, in which the work continued very actively, with possibilities of acting in new places, with new opportunities, nevertheless being still exercised by most of them, in the same follow-up (research, teaching and extension). They reported emphatically the opportunity to work without the need to comply with strict hours, and to use the time in a freer and more organized way for other daily demands. The experience of aging has taken on different meanings, being pointed at times as difficult to accept and, in others, as a possibility of learning, reflection and wisdom. This point out that aging is linked to a physical and emotional condition that is very particular to each one and that is anchored in a set of experiences. In both cases, the physical limitations were not neglected. New research notes, with analyzes directed to the same category of work, however with high school teachers and / or private institutions, which relate the theme presented here, are made at the end of this study, as recommendations for future studies.